The last forty years of the history of the Educational Inspection in Spain - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2010)
This article analyses the parallelism between the evolution of educational system itself and the hazardous evolution -with professional upheavals- carried out by the Inspectorate of Education throughout the latest period in its history, since 1970 onwards. This period of time began with the coming in force of the General Act of Education -widely known as Villar Palasí Act and named after the Minister of Education in office at that time-, and lasts until the present day with the fully development of the 2006 Organic Act of Education.